Studies on 12% Reinforced Aluminium Based Metal Matrix Composites - Patel, AS; Sankhla, AM; Bagga, PJ (International Journal of Computer Sciences and Engineering, 2025)
It is always endeavor of ongoing research in material science to take advantage of specific or particular properties of the constituent material present in a composite material. Aluminum based metal matrix composites have been developed to tailor the properties. Aluminum is a preferred choice for metal matrix composites (MMC) for several reasons like low density, high thermal and electrical conductivity and good damping capacity. Aluminium metal matrix composites (Al-MMCs) exhibit improved mechanical properties, when reinforced by ceramics like Al2O3 and SiC. This paper presents an experimental study to produce Al-MMC by powder metallurgy process in which fine aluminum powder reinforced by ceramic particles like SiC and Al2O3 by 12% of its total weight. The green compact was produced using a set of die and punch. The necessary compaction of blended powder obtained using a mounting press. Sintering of green compact carried out at temperature of 95% of melting point of matrix material for 1 hour. The study of density, hardness, compressive strength and dry sliding wear capability of fabricated MMC is attempted. The average hardness of MMC increased by 2-3 times as compared to pure commercial aluminium with deviation of 11% in the density obtained experimentally.